232 Micromedullary Thyroid Carcinoma: A Clinicopathologic Review. (11th January 2018) - Rohra, Prih; Mahmud, Waqas; Bitterman, Pincas; Reddy, Vijaya; Gattuso, Paolo
Abstract: Objectives: Micromedullary thyroid carcinoma is defined as tumor measuring ≤1 cm in greatest dimension. We performed a retrospective study to assess the clinical significance and the pathologic findings associated with micromedullary thyroid carcinoma. Methods: The surgical pathology files from 1995 to 2017 at our institution were reviewed for medullary thyroid carcinoma. Results: A total of 33 cases of medullary thyroid carcinoma were recorded, of which 13 (39%) qualified as micromedullary carcinoma (≤1 cm). Seven patients were male and six female, with age range of 9 months to 72 years (mean of 48 years). All patients except one underwent a total thyroidectomy. The tumor size ranged from 1 mm to 8 mm with a mean of 4 mm. Two tumors were multifocal. Seven of 13 (53%) patients had selective neck sampling or lymph node dissection. Two of seven (28%) had lymph node metastasis. The primary tumor size was 6 and 8 mm. None of the tumors (nine cases) with a size of ≤5 mm had evidence of regional lymph node involvement. Other significant pathologic findings included synchronous papillary carcinoma in six of 13 (46%) (mean size was 1 cm), synchronous hyperparathyroidism (MEN1 syndrome) in three of 13 and concomitant paraganglioma (MEN2A syndrome) in one patient. Conclusion: In our study, 39% of medullary carcinomas qualified as micromedullary carcinoma, and 28% cases with lymph node sampling showed metastatic medullary carcinoma. Forty-six percent of cases had concomitant papillary carcinomas, most likely a coincidence. 30% were associated with MEN1 and MEN2 syndromes. Since none of the tumors measuring ≤5 mm showed regional lymph node disease, redefinition of micromedullary carcinoma should be explored.